Blumhouse productions : the new house of horror - Platts, Todd K.; McCollum, Victoria; Clasen, Mathias F. (University of Wales Press, 2022)
"Blumhouse Productions: The New House of Horror provides the first sustained academic inquiry into one of the biggest production companies currently working in horror film production. Scholars from a wide range of disciplines explore various facets of the company, which is known for such hit franchises as Paranormal Activity, Insidious, and The Purge, in addition to critically acclaimed works such as Get Out, and box office sensations such as Happy Death Day and Split. Balancing attention to the behind-the-scenes workings of the company and its productions with accounts of the films themselves, the book presents a thorough and detailed picture of Blumhouse Productions and its cultural footprint."--Publisher description.
Keywords: Blumhouse Productions; Horror films -- Production and direction.; Films d'horreur -- Production et réalisation.; Horror films -- Production and direction; FICTION / Horror